Are Islamic banks different? The application of the Radical Affinity Index. Issue 1 (4th March 2019) - San-Jose, Leire; Cuesta, Jon
Abstract : Purpose: The purpose of this paper is to extend the literature on Islamic banking by examining their ethical dimension using transparency, placement of assets, guarantees and participation from Radical Affinity Index. Design/methodology/approach: To this end, a sample of 20 Islamic banks from 13 countries (Bahrain, Saudi Arabia, Malaysia, Pakistan, Kuwait, Tanzania, Great Britain, Oman, Iraq, Egypt, Bangladesh and Qatar) was used. Findings: The results are robust to ethical effects. The evidence suggests that among Islamic banks, at least some of them could improve their ethical requirements of the Sharia; they obtained lower scores than ethical banks in terms of RAI variables (transparency, placement of assets, guarantees and participation). Research limitations/implications: It is used a random sample rather than population with the limitations that entails. The variables in the index are based on ethical perspective; then, the index is applied in Islamic banking but with the ethical view limitation. Practical implications: The Islamic banks have the option to increase their transparency including further information regarding the beneficiaries of the benevolent funds; moreover, it would offer a clearer view about their ethical and social commitment towards society. Originality/value: Additionally, this paper broadens the scope of the literature by analysing the determinants of Islamic banking around ethical dimensions of financial entities.